Mitogenome of a cryptic species within Uropsilus and divergence time estimation - Yu Xu; Yunting Hu; Feiyun Tu (Mitochondrial DNA. Part B. Resources, 2017)
Uropsilus sp. 4 is a new cryptic species, collected in Changyang county, Hubei province, China. In this study, the whole mitochondrial genome of Uropsilus sp. 4 was first determined and characterized. The genome is 16,542 bp in length, containing 13 protein coding genes, 22 transfer RNA genes, two ribosomal RNA genes, and a putative control region. Base on NJ, ML, and BI methods, we obtained the same topologies. U. sp. 4 clustered with U. gracilis and the divergence time was 1.78 Ma (95% CI 1.24–2.32 Ma), in concordance with the third period of last orogenic push of the Qinghai-Tibetan Plateau, might contribute to the speciation of U. sp. 4.